The Role of International Security Institutions in The Emerging International Order: The United States and China as Vital Stakeholders - Elmir Fioreze, Rafaela; Chaves Cepik, Marco Aurélio (Revista de Geopolítica, 2023)
The contemporary security multilateral institutional framework is characterized by varied functional and geographical configurations, regimes, alliances, and dialogue fora. Some recent events and trends, such as the disintegration of the US-Russia arms control regime and the growing incapacity of multilateral organisms such as the United Nations Security Council, suggest, nonetheless, that this framework is in crisis. This article aims to explain the current crisis in the realm of peace and security multilateralism and the roles of the United States and China in this context. We conclude that the Global South actors need to exert their collective agency demanding more inclusive and cohesive security multilateral institutions to help manage great power rivalry in a way that better suits the collective aims of peace and development on a global scale.